Effect of blended learning on students’ ability level and achievement in senior secondary geography in three education zones in niger state, Nigeria - Abubakar Yahya Ibrahim (Cahaya Ilmu Cendekia Publisher, 2020)
Purpose of the study: The purpose of this study was to determine the effect of student ability levels on the average value (x̄) of academic achievement of students in geography and the influence of method interactions and abilities on the average achievement score (x̄) of students in geography Methodology: The research design for the study was Quasi-experimental. Niger is one of the 36 States in Nigeria, the state is bordered by Zamfara State in the North, Kebbi State and Benin Republic in North West, Kaduna State in the North East, In the South it is bordered by Kogi State, South West by Kwara State and South East by Federal Capital Territory (FCT) Abuja (Source: Geography Department FUT, Minna and Ministry of Land and Survey-Niger State, Minna). Main Findings: High ability level students had higher mean (x̄) achievement score that the low ability level students Also there is a significant difference between the mean (x̄) the achievement scores of low and high ability level students. Low ability level students who were taught geography using BLM had higher mean gain achievement score than the low ability level students taught using lecture methods while the high level ability students who were taught using BLM had higher mean gain achievement score than the high ability students taught using lecture method. It was further revealed that there is no significant interaction effect of method and ability level on the mean achievement scores in Geography.